(untitled) (Journal of Laboratory Animal Science, 2024)
Detection of pathogenic organisms in any module of the conventionally bred animal facility is suggestive of possible infection in other strains/ modules of the facility as well. Timely diagnosis of the microbes prevailing in the conventional animal facility is possible if well planned screening program is in place. Laboratory Animal Facility of ACTREC breed and maintains 22 different strains of mice, two strains of hamsters and one rat strain. This paper report the microbiological screening results of rodent pathogens prevailing in the Laboratory animal Facility, ACTREC, India. Microbiological status of these strains was assessed by conventional microbiology using agar media and biochemical tests; readymade ELISA kits and PCR methods. Results of the conventional microbiology revealed that the rodents in ACTREC were reported positive for Klebsiella pneumoniae, Staphylococci aureus, Escherichia coli and Proteus sp. Recent ELISA based results revealed presence of Mycoplasma pulmonis, CAR bacilli, Sendai, Tyzzer’s disease, MHV, Helicobacter hapaticus, Polyoma, Minute virus of mice, Pneumocystis carinii, Pasturella pneumotropica and Mouse Parvovirus; whereas PCR based methods revealed presence of Mycoplasma pulmonis, Sendai, Helicobacter hapaticus, Pneumocystis carinii, Helicobacter bilis, MNV, MHV and CAR bacilli. Effective quarantine, barrier maintenance, frequent surveillance for all recommended pathogens and eradication of the existing pathogens is the challenge to be accepted.